International consensus guidelines on Clinical Target Volume delineation in rectal cancer. Issue 2 (August 2016) - Valentini, Vincenzo; Gambacorta, Maria Antonietta; Barbaro, Brunella; Chiloiro, Giuditta; Coco, Claudio; Das, Prajnan; Fanfani, Francesco; Joye, Ines; Kachnic, Lisa; Maingon, Philippe; Marijnen, Corrie; Ngan, Samuel; et al.
Abstract: Introduction: The delineation of Clinical Target Volume (CTV) is a critical step in radiotherapy. Several guidelines suggest different subvolumes and anatomical boundaries in rectal cancer (RC), potentially leading to a misunderstanding in the CTV definition. International consensus guidelines (CG) are needed to improve uniformity in RC CTV delineation. Material and methods: The 7 radiation oncologist experts defined a roadmap to produce RC CG. Step 1: revision of the published guidelines. Step 2: selection of RC cases with different clinical stages. Step 3: delineation of cases using Falcon following previously published guidelines. Step 4: meeting in person to discuss the initial delineation outcome, followed by a CTV proposal based on revised and if needed, adapted anatomical boundaries. Step 5: peer review of the agreed consensus. Step 6: peer review meeting to validate the final outcome. Step 7: completion of RC delineation atlases. Results: A new ontology of structure sets was defined and the related table of anatomical boundaries was generated. The major modifications were about the lateral lymph nodes and the ischio-rectal fossa delineation. Seven RC cases were made available online as consultation atlases. Conclusion: The definition of international CG for RC delineation endorsed by international experts might support a future homogeneous comparison between clinical trial outcomes.